A new species of Litarachna (Acari, Hydrachnidia, Pontarachnidae) from a Caribbean mesophotic coral ecosystem - Pešić, Vladimir (Pensoft Publishers, 2014)
Abstract. New records of pontarachnid mites (Acari: Hydrachnidia) from the Caribbean island of Puerto Rico are presented. Litarachna lopezae sp. n., from substrata collected from Bajo de Sico, a mesophotic coral reef ecosystem in Mona Passage off Puerto Rico, is described as new to science. The new species was collected from nearly 70 m depth, the greatest depth from which pontarachnid mites have been found until now. In addition, a Litarachna sp. was also found in association with the tube of the polychaete Sabellastarte magnifica (Shaw, 1800) at the shallow waters of north Puerto Rico.